EFEKTIVITAS MANAJEMEN SURAT MENYURAT DI LINGKUNGAN SEKOLAH DASAR - Oding Supriadi (Universitas Singaperbangsa Karawang, 2020)
Letters convey information related to the educational, learning, and social processes in the school environment, especially elementary schools. Besides, letters are data or information centers that are very useful in the ongoing education process, especially in elementary schools. Therefore, from the start of making and filing letters need special attention, so that information or data can be accounted for formally. For that, we need good correspondence management for each school, especially elementary schools. The purpose of this article is to provide information on how to describe correspondence management at the elementary school level in Pagaden sub-district, Subang district, West Java province through interviews and direct observation.